Computers and Advanced Technology in Education 2012
DOI: 10.2316/p.2012.774-062
|View full text |Cite
|
Sign up to set email alerts
|

A Pattern-based and Teacher-Centered Approach for Learning Design

Abstract: Teaching is changing in deep, due to, on one hand, the evolutions of the society expectations and, on another hand, the widely spreading of new technologies. By the way, teachers and trainers need now to structure and formalize their internal designs and should become designers but do not have the competence. We aim to help them during the instructional design process. In that way we propose some methods and tools to support the scenario design activity and the implementation of the resulting models. We presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…According to the DSM approach, a meta-model (Clayer et al, 2012) has been defined to describe the language of patterns. This language use four formalisms of patterns: Pedagogical Patterns, Analysis Patterns, Process Patterns and Design Patterns.…”
Section: A Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the DSM approach, a meta-model (Clayer et al, 2012) has been defined to describe the language of patterns. This language use four formalisms of patterns: Pedagogical Patterns, Analysis Patterns, Process Patterns and Design Patterns.…”
Section: A Patternsmentioning
confidence: 99%
“…This form presents only the most important element of a pattern: a name, a problem, a context and a solution. We represents the activity "Realize an individual evaluation/training" by a process-pattern according to the meta-model (Clayer et al, 2012). The problem and context are in a textual form.…”
Section: A Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of practitioners' needs (Figure 1 -left) and the formalization of the LMS instructional design domain (Figure 1 -right) are the prerequisites and first blocks for the GraphiT project. They have already provided some results (Clayer et al, 2012;. The project main issue and objective (Figure 1 -center) has been investigated through the initial exploratory works, explained in this paper.…”
Section: The Graphit Projectmentioning
confidence: 99%
“…We take into account these elements within four categories of pedagogical problem: Activity design, Learning situations design, Resources design and Pedagogy design. According to the design problems highlighted in teaching domain, (Clayer et al, 2012) explored the TEL engineering domain best practices (Mor and Winters, 2007); (Mor, 2010); (Laurillard, 2012); (Rohse and Anderson, 2006); (Bergin et al, 2012) and the software engineering patterns solutions implemented in the information system domain (Fowler, 1997) (Amber, 1998) (Gamma et al, 1995). These authors identified four formalisms of patterns to solve the four types of problem: Pedagogical patterns; Analysis Patterns, Process Patterns and Design Patterns.…”
Section: Design and Patternsmentioning
confidence: 99%